Enteric Fever in South China: Guangxi Province - Jin Yang (The Journal of Infection in Developing Countries, 2008)
Guangxi is a province of China endemic for enteric fever. Salmonella enterica serovar Paratyphi A has been found to be causing more and more enteric fever episodes in the last 10 years, evident not only from routine surveillance but also from prospective population-based surveillance. The prevalent pattern of paratyphoid seen was different from typhoid since it mainly occurred in outbreaks. Almost all strains collected from different areas and years in Guangxi were resistance to nalidixic acid, which is an indicator of reduced efficacy of ciprofloxacin treatment. The emergence of epidemic paratyphoid fever occurred after large-scale use of the typhoid Vi vaccine, but little is know about why it emerged. This is of particular concern in the post Vi vaccine era due to the emergence and worldwide spread of multi-drug resistant S. Paratyphi A strains and the lack of a vaccine.